THE USE OF ICT IN WRITING ENGLISH IN PANDEMIC OF COVID-19 PERIOD ON MIDWIFERY STUDENTS OF STIK BINA HUSADA AND STIKES PEMBINA PALEMBANG - Arief Pamuji (Language and Education Journal, 2020)
The objective of this research was to find out the description of the use of ICT in writing English in a pandemic of Covid-19 periods on midwifery students of STIK Bina Husada and STIKES Pembina Palembang, The sample of this research was taken by using totaling sampling technique with 97 midwifery students from both institutions. The data were obtained based on every meeting during online learning, which was from the third meeting to the seventh meeting that consists of five days for obtaining the data. Then from the data analysis, it’s obtained that there was a good improvement response by writing English related to the material since the first day to the fifth day that was 63% of students responded to the 95% students' response on the last day. During the implementation of online learning by using ICT (Whatsapp group and Edlink) the obstacle raised on students. Many factors that made the students cannot join the class and respond. One of the factors was access to the internet in their hometown. Even had the obstacle the use of ICT can be a good choice in conducting the teaching and learning EFL process of midwifery students of STIK Bina Husada and STIKES Pembina Palembang